Thailand : Financial Sector Assessment Program; Detailed Assessment of Observance of CPSS Core Principles for Systemically Important Payment Systems. (IMF Staff Country Reports; Country Report, 2009)
This paper focuses on a detailed assessment of observance of the Committee on Payment and Settlement Systems (CPSS) core principles for systemically important payment systems in Thailand. This assessment covers the Bank of Thailand Automated High-Value Transfer Network (BAHTNET), which is a real-time gross settlement (RTGS) system. The assessment reveals that there is no explicit legislation for payment systems in Thailand. However, the legal basis for BAHTNET and payment transfers executed in this system is defined by a set of laws, regulations, and contractual arrangements.